1996
DOI: 10.1097/00002820-199606000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study on quality of life and social support in cancer patients

Abstract: The aim of the present study is to acquire insight into the changes of quality of life, social networks, and social support of cancer patients during the first year after diagnosis, as well as into the relation between social support and the changes in quality of life. Newly diagnosed cancer patients (n = 51) were followed for 1 year. Semistructured personal interviews and questionnaires were used to gather data. On the average, patients' functioning improved and the amount of physical complaints decreased ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
98
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(115 citation statements)
references
References 18 publications
15
98
1
1
Order By: Relevance
“…Patients' family and their loved ones can be very supportive during early illness trajectories. On the other hand, one longitudinal study on QOL and social support in cancer patients reported that network size and the amount of received emotional support decreased somewhat over time [14]. This decrease may be related to a reduction in the availability of needed support as well as a reduction in the perceived quality of support, when available [15].…”
Section: Int Conf Society Health Welfare 2014mentioning
confidence: 99%
“…Patients' family and their loved ones can be very supportive during early illness trajectories. On the other hand, one longitudinal study on QOL and social support in cancer patients reported that network size and the amount of received emotional support decreased somewhat over time [14]. This decrease may be related to a reduction in the availability of needed support as well as a reduction in the perceived quality of support, when available [15].…”
Section: Int Conf Society Health Welfare 2014mentioning
confidence: 99%
“…In previous research, patients and caregivers have reported anxiety and distress resulting from social isolation, stigmatization, feeling misunderstood and an inability to talk about their feelings or situation. 3,14,15 Both professional and informal social support are central to adapting to illness. 3,16 Patients with glioma have reported lower social support as their disease progressed and their functional abilities deteriorated.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…3,16 Patients with glioma have reported lower social support as their disease progressed and their functional abilities deteriorated. 14 Recognizing that a person's desired level of social support may increase with greater need is vital to maximizing such support.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Patients undergoing radiotherapy received most support from family and friends and the support the patients expected and received from professionals was informational support (Hinds & Moyer 1997). Courtens et al (1996) conducted a longitudinal study of newly diagnosed cancer patients' social network and social support. They found no relation between structural aspects of network, measured by size, density and composition of the network, and QoL, but emotional support was positively related to QoL (Courtens et al 1996).…”
Section: Social Supportmentioning
confidence: 99%
“…Courtens et al (1996) conducted a longitudinal study of newly diagnosed cancer patients' social network and social support. They found no relation between structural aspects of network, measured by size, density and composition of the network, and QoL, but emotional support was positively related to QoL (Courtens et al 1996).…”
Section: Social Supportmentioning
confidence: 99%